Influences of Stress and Sex on the Paraventricular Thalamus: Implications for Motivated Behavior - Rowson, Sydney A.; Pleil, Kristen E. (Frontiers in Behavioral Neuroscience, 2021)
The paraventricular nucleus of the thalamus (PVT) is a critical neural hub for the regulation of a variety of motivated behaviors, integrating stress and reward information from environmental stimuli to guide discrete behaviors via several limbic projections. Neurons in the PVT are activated by acute and chronic stressors, however several roles of the PVT in behavior modulation emerge only following repeated stress exposure, pointing to a role for hypothalamic pituitary adrenal (HPA) axis modulation of PVT function. Further, there may be a reciprocal relationship between the PVT and HPA axis in which chronic stress-induced recruitment of the PVT elicits an additional role for the PVT to regulate motivated behavior by modulating HPA physiology and thus the neuroendocrine response to stress itself. This complex interaction may make the PVT and its role in influencing motivated behavior particularly susceptible to chronic stress-induced plasticity in the PVT, especially in females who display increased susceptibility to stress-induced maladaptive behaviors associated with neuropsychiatric diseases. Though there are literatures describing the sex-specific effects of acute and chronic stress exposure on HPA axis activation and on motivated behaviors, the impact of sex on the role of the PVT in modulating the behavioral and neuroendocrine response to stress is less well established. Here, we review what is currently known regarding the acute and chronic stress-induced activation and behavioral role of the PVT in male and female rodents. We further explore stress hormone and neuropeptide signaling mechanisms by which the HPA axis and PVT interact and discuss the implications for sex-dependent effects of chronic stress on the PVT’s role in motivated behavior.